Pendidikan Agama Islam dalam Tuntunan Syariat Rasulullah SAW - Imam Tabroni; Dyah Erawati; Imam Maspiah; Hilma Sa’adatunnisa (Indra institute Research & Publication, 2022)
Islamic education is education that must be instilled as early as possible, even from the time of a mother’s womb. Because basically informal education is the beginning of the development of the child’s character is formed. Children who are happy in family care will bring up good character and are friendly to their environment when he enter the formal and non-formal education environment the will be more dominant and confident. Islamic religious in formal and non-formal schools must be further developed, especially in teaching the character of the personality of students. The problem formulation of this research is how Islamic religious education can be used as a reference in formal and non-formal educational institutions as a way to rediscover the character of students who excel and have good morals according to the guidance of the Prophet SAW. It is intended that Islamic religious education can be used as a benchmark for educational institutional in producing generation of good morals. This education uses the literature review method because in the process of collecting data it takes several book sources as a references. Then used descriptive qualitative to analyze the research that is in the form of a systematic systematic sentence according to the source of the reference.